Implementation Program of the School Operational Assistance: A Case Study in Berau District: A Case Study in Berau District - Dewi Sugesti; Syachrumsyah Asri; Sudirah Sudirah (International Journal of Community Service & Engagement, 2022)
School Operational Assistance (SOA) is a government program to improve the quality and quality of learning in state schools. Yet, SOA reporting was colored by delays by various schools. Reporting must be under regional financial administration. On the other hand, schools are required to make reports according to the format from the Ministry of Education and Culture of the Republic of Indonesia. Through this paper, the author analyzes the implementation of the SOA policy at the elementary (SD) and junior high school (SMP) levels. Too, we also analyze the factors that support and hinder the implementation of the policy in public schools in Berau District. This study uses a descriptive method with a case-qualitative study. Referring to absorption capacity, effectiveness, accountability, transparency, implementer commitment, goals and targets, as well as analyzing the factors that influence SOA policy, it shows that its actualization in schools located in the city center have "good" absorption and effectiveness, while schools located in far from the city center is categorized as “moderate”. Accountability, transparency, commitment of implementers in general have gone well. Thus, schools that are far from the city center are still not optimal, for example in providing information related to the use of SOA. The goals and objectives of the SOA program have been achieved, but the financing of competency standards in schools is still inadequate. The analysis shows that the lack of appropriateness of this program is triggered by the lack of communication, human resources, bureaucratic structure, and characteristics of the implementer. Therefore, it needs serious attention from implementers, schools, and local governments to find solutions, especially in providing support for increasing competence, especially school principals and treasurers so that this policy can be accounted for in a transparent and accountable manner.